2019
DOI: 10.1021/acs.jpcb.9b00963
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Properties of Ionic Liquids: Electrostatics, Structure Factors, and Their Sum Rules

Abstract: The properties of room-temperature ionic liquids (ILs) may be viewed as resulting from a balance of electrostatic interactions that can be tuned at short range but constrained to satisfy universal, asymptotic screening conditions. Short-range interactions and ion packing provide ample opportunity for chemical tunability, while asymptotic sum rules dictate that the long-range structure and charge oscillation be similar to those of molten alkali halide salts. In this work, we study the structure factors and long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 67 publications
5
71
0
Order By: Relevance
“…Figure S10 for [BMIM + ][TFSI − ]/water mixtures. All systems show a peak at ∼0.6-0.7 nm lengthscale, which reflects the characteristic anion separation distance in the corresponding neat IL [111]. This peak is the closest anion separation distance in the mixtures and is present at all concentrations.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…Figure S10 for [BMIM + ][TFSI − ]/water mixtures. All systems show a peak at ∼0.6-0.7 nm lengthscale, which reflects the characteristic anion separation distance in the corresponding neat IL [111]. This peak is the closest anion separation distance in the mixtures and is present at all concentrations.…”
Section: Resultsmentioning
confidence: 85%
“…This peak is the closest anion separation distance in the mixtures and is present at all concentrations. For neat ILs, it has been shown that this 0.6-0.7 nm lengthscale corresponds to oscillations of shells of counterions within the liquid [111]. It is notable that addition of water does not give rise to a closer distance anion/anion peak, which might be expected for solvent separated anion pairs.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations